2018
DOI: 10.1111/emip.12186
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Decision Accuracy of Complex Compensatory Decision Rules Combining Multiple Tests in a Higher Education Context

Abstract: This real‐data‐guided simulation study systematically evaluated the decision accuracy of complex decision rules combining multiple tests within different realistic curricula. Specifically, complex decision rules combining conjunctive aspects and compensatory aspects were evaluated. A conjunctive aspect requires a minimum level of performance, whereas a compensatory aspect requires an average level of performance. Simulations were performed to obtain students' true and observed score distributions and to manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…On the one hand, higher performance standards have consistently been associated with higher grades (Johnson and Beck 1988;Elikai and Schuhmann 2010;Kickert et al 2018Kickert et al , 2019, which should result in higher progress. Additionally, simulation studies have shown that more students progress in case of compensatory instead of conjunctive standards (Douglas and Mislevy 2010;Yocarini et al 2018). On the other hand, a higher performance standard is harder to pass, which may result in lower progress (Yocarini et al 2018).…”
Section: Performance Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, higher performance standards have consistently been associated with higher grades (Johnson and Beck 1988;Elikai and Schuhmann 2010;Kickert et al 2018Kickert et al , 2019, which should result in higher progress. Additionally, simulation studies have shown that more students progress in case of compensatory instead of conjunctive standards (Douglas and Mislevy 2010;Yocarini et al 2018). On the other hand, a higher performance standard is harder to pass, which may result in lower progress (Yocarini et al 2018).…”
Section: Performance Standardmentioning
confidence: 99%
“…Additionally, simulation studies have shown that more students progress in case of compensatory instead of conjunctive standards (Douglas and Mislevy 2010;Yocarini et al 2018). On the other hand, a higher performance standard is harder to pass, which may result in lower progress (Yocarini et al 2018). Due to these two opposing influences of higher performance standards on academic progress, it is difficult to predict whether progress will be affected by an altered performance standard in real life.…”
Section: Performance Standardmentioning
confidence: 99%
“…Firstly, providing more resit opportunities has been associated with lower performance on the initial assessment, although more resit opportunities were not associated with differences in final grades (Grabe 1994). Secondly, a resit is an extra opportunity to pass an assessment by chance (Yocarini et al 2018). Thirdly, resits may offer an unfair advantage to the resit students, for instance due to additional practice opportunities (Pell, Boursicot, and Roberts 2009).…”
Section: Assessment Policiesmentioning
confidence: 99%
“…Rather, there are some conjunctive aspects included in which a minimum level of performance is required. Previous research, in which the argument that the average grade is more reliable was evaluated, shows that the required minimum grade is also important for the accuracy of the compensatory rule (Yocarini et al 2018). Furthermore, the results of this study show that the accuracy of a compensatory decision rule relative to a conjunctive decision rule depends on the test reliabilities, correlation between tests, and the number of resits allowed.…”
Section: Allowing Course Compensationmentioning
confidence: 54%